2015
DOI: 10.2147/dddt.s85426
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatic and mechanistic study elicits the antifibrotic effect of ursolic acid through the attenuation of oxidative stress with the involvement of ERK, PI3K/Akt, and p38 MAPK signaling pathways in human hepatic stellate cells and rat liver

Abstract: NADPH oxidases (NOXs) are a predominant mediator of redox homeostasis in hepatic stellate cells (HSCs), and oxidative stress plays an important role in the pathogenesis of liver fibrosis. Ursolic acid (UA) is a pentacyclic triterpenoid with various pharmacological activities, but the molecular targets and underlying mechanisms for its antifibrotic effect in the liver remain elusive. This study aimed to computationally predict the molecular interactome and mechanistically investigate the antifibrotic effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…As a traditional Chinese medicine, UA can inhibit the proliferation of activated HSCs, induce apoptosis, and protect liver cells to exert anti-fibrotic effects [ 41 ]. We conducted a preliminary exploration of the target of UA in HSCs and found that UA can inhibit the proliferation and migration of HSCs by inhibiting the NOX4/ROS and RhoA/ROCK1 signalling pathways, and this result was further verified in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Chinese medicine, UA can inhibit the proliferation of activated HSCs, induce apoptosis, and protect liver cells to exert anti-fibrotic effects [ 41 ]. We conducted a preliminary exploration of the target of UA in HSCs and found that UA can inhibit the proliferation and migration of HSCs by inhibiting the NOX4/ROS and RhoA/ROCK1 signalling pathways, and this result was further verified in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…P38MAPK and ERK1/2 may regulate oxidative stress and inflammatory responses [34, 35]. It is known that many I/R injury models elicited the activation of p38MAPK and ERK1/2 pathways [3638].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers subsequently corroborated that UA selectively induces the apoptosis of activated HSCs without inducing liver or quiescent HSC apoptosis (Wang et al, 2011). Furthermore, we observed that UA inhibited the leptin-mediated expression of the NOX subunits NOX2, P67phox and NOX4 in an activated rat HSC cell line (HSC-T6), resulting in the accumulation of extracellular matrix (ECM) proteins (Wang et al, 2011; He et al, 2015). In addition, the results of another study suggested that UA attenuates experimental colitis in mice via its anti-inflammatory and antioxidant activities (Chun et al, 2014; Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 98%